(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Review of a solar tracking system the greatest problem for the next half-century will be generating electricity from the decrease of fossil fuels. When compared to other renewable energy sources, the concept of turning solar energy into electrical energy using photovoltaic panels is at the top of the list. However, the sun’s relative angle is always changing. The number of watts supplied by a solar panel is reduced when measured in relation to the earth. In this case, a solar tracking system is used. The most efficient way to boost the efficiency of a solar panel. The payload is moved using solar trackers during the day, towards the sun. Different kinds of tracking systems are discussed in this article. Their advantages and disadvantages are thoroughly addressed. The findings of this study show that the azimuth is correct. In comparison to other tracking systems, the altitude dual axis tracking system is more efficient. However, in the standpoint of cost and flexibility a single-axis tracking system is more practical than a dual-axis system.